Edukasi Kesehatan Remaja dan Pengelolaan Sampah Organik untuk Pencegahan DBD di SMPN 3 Ubud - Anny Eka Pratiwi; I Dewa Ayu Eka Pertiwi (Lembaga Pengembangan Kinerja Dosen, 2026)
The health-related issues identified indicate that students have not yet developed sufficient skills in managing the School Health Unit (UKS), and existing health education programs have not been implemented optimally. From an educational perspective, students are proficient in only one foreign language, namely English, which may limit their broader communication competencies. Economically, many students’ parents work as traders and tour guides, highlighting the importance of equipping students with basic entrepreneurial and financial management skills from an early age. Socially and culturally, instances of bullying have been reported, while from an environmental perspective, students demonstrate limited understanding of proper organic and non-organic waste management. Based on fields assessment, the priority issues identified include strengthening adolescent health programs and utilizing school land to support food security initiatives. In response, the community service implementation team formulated integrated solutions addressing adolescent health, environmental health, and economic empowerment. In the health sector, the intervention focused on adolescent health education emphasizing reproductive health, balanced nutrition, and clean and healthy living behaviors. To support environmental health, demonstrations on processing organic waste into compost and using it as planting media for vegetables and fruits within the school environment were conducted, aiming to reduce mosquito breeding and prevent dengue transmission. In the economic sector, mental accounting training was provided to improve students’ financial literacy and personal financial management skills. The activities were delivered through presentations and interactive discussions. The results indicate that the program was effective as a promotive and preventive strategy to improve adolescent health and financial awareness.